Influence of heat treatment modes on the performance characteristics of resistive cermet coatings - Kovbasiuk, Taras; Duriagina, Zoia; Kulyk, Volodymyr; Pleshakov, Eduard; Kushpir, Vasyl (Lviv Politechnic Publishing House, 2020)
Dielectric and resistive coatings based on glass ceramics with nickel boride additives have been synthesized. It was found that the microstructure of the resistive coating consists of a large number of phases. X-ray fluorescence analysis revealed the presence of Ni and Cr borides in the structure of the resistive layer. It was found that the change in the structure and specific surface resistance of resistive pastes practically does not affect the temperature coefficient of resistance of the synthesized resistive tracks.
Keywords: film heating element, cermet, microstructure, glass-ceramic, coating